2023
DOI: 10.3389/fchem.2023.1141453
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship of Cu-based catalysts for the highly efficient CO2 electrochemical reduction reaction

Abstract: Electrocatalytic carbon dioxide reduction (CO2RR) is a relatively feasible method to reduce the atmospheric concentration of CO2. Although a series of metal-based catalysts have gained interest for CO2RR, understanding the structure–activity relationship for Cu-based catalysts remains a great challenge. Herein, three Cu-based catalysts with different sizes and compositions (Cu@CNTs, Cu4@CNTs, and CuNi3@CNTs) were designed to explore this relationship by density functional theory (DFT). The calculation results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Modulation of the catalyst’s surface composition by alloying can directly change the intermediates in their absorption state at the active site and determine the final product during the CO 2 RR process. Therefore, alloying is an effective strategy to adjust the electronic structure and improve the activity and selectivity of CO 2 RR …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Modulation of the catalyst’s surface composition by alloying can directly change the intermediates in their absorption state at the active site and determine the final product during the CO 2 RR process. Therefore, alloying is an effective strategy to adjust the electronic structure and improve the activity and selectivity of CO 2 RR …”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, there is an urgent need to design cheap, safe, efficient, and highly selective electrocatalysts to improve the slow kinetics and energy conversion efficiency. 12,13 As early as the 1990s, Hori et al 14 demonstrated that different pure metal catalysts could be used as catalysts for accelerated electrocatalytic CO 2 RR, but their large-scale production and practical applications were limited due to the problems of high cost, poor performance, and poor selection. For example, although the metal Cu has been repeatedly shown to catalyze CO 2 to valuable hydrocarbons or alcohols, it has high overpotentials and a large number of byproducts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations